2021
DOI: 10.3390/ani11092489
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Comparisons of Chelonid Alphaherpesvirus 5 (ChHV5) Genomes from Fibropapillomatosis-Afflicted Green (Chelonia mydas), Olive Ridley (Lepidochelys olivacea) and Kemp’s Ridley (Lepidochelys kempii) Sea Turtles

Abstract: The spreading global sea turtle fibropapillomatosis (FP) epizootic is threatening some of Earth’s ancient reptiles, adding to the plethora of threats faced by these keystone species. Understanding this neoplastic disease and its likely aetiological pathogen, chelonid alphaherpesvirus 5 (ChHV5), is crucial to understand how the disease impacts sea turtle populations and species and the future trajectory of disease incidence. We generated 20 ChHV5 genomes, from three sea turtle species, to better understand the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 74 publications
0
6
0
3
Order By: Relevance
“…To date, there have been many microbiological studies on sea turtles. Several studies have demonstrated that Chelonid Alphaherpes virus 5 (ChHV5) causes fibropapillomatosis (FP) in the head and extremities of sea turtles, which can lead to restricted movement and reduced feeding ability ( 8 10 ). Previous studies have shown that environmental pollution, while correlated with habitat destruction, has no impact on ChHV5.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there have been many microbiological studies on sea turtles. Several studies have demonstrated that Chelonid Alphaherpes virus 5 (ChHV5) causes fibropapillomatosis (FP) in the head and extremities of sea turtles, which can lead to restricted movement and reduced feeding ability ( 8 10 ). Previous studies have shown that environmental pollution, while correlated with habitat destruction, has no impact on ChHV5.…”
Section: Introductionmentioning
confidence: 99%
“…ChHV5 consensus genome generation from sand eDNA and phylogenetic analysis was conducted as previously described in Whitmore et al (2021), for the sample with sufficient ChHV5 aligning reads (patient "Archie").…”
Section: Dna Sequencingmentioning
confidence: 99%
“…Fibropapilloma tumours have been also observed in olive ridleys nesting on the Pacific coasts of Costa Rica [ 109 , 113 ], in “La Escobilla” sanctuary in Oaxaca, Mexico [ 114 ], in Nicaragua [ 115 ], in India [ 116 ], and foraging off the Pacific coast of Mexico [ 117 , 118 ]. Recently, FP has been reported in olive ridleys stranded in Chile [ 119 ] and in the U.S. [ 106 , 120 ]. Reports and sightings of olive ridley turtles with FP in Pacific and Atlantic waters, as well as nesting beaches, are becoming more and more frequent.…”
Section: Vulnerabilities and Threats For The Olive Ridley Turtlementioning
confidence: 99%